Altered activation and connectivity of the supplementary motor cortex at motor initiation in Parkinson's disease patients with freezing. Issue 9 (September 2020) - Brugger, Florian; Wegener, Regina; Walch, Julia; Galovic, Marian; Hägele-Link, Stefan; Bohlhalter, Stephan; Kägi, Georg
Highlights: The Bereitschaftspotential is smaller in Parkinson's disease patients with freezing of gait. Cortical beta oscillations are increased prior to volitional movements in patients with freezing. Repetitive transcranial magnetic stimulation leads to deteriorated gait initiation. Abstract: Objective: Motor initiation failure is a key feature of freezing of gait (FOG) due to Parkinson's disease (PD). The supplementary motor cortex (SMC) plays a central role in its pathophysiology. We aimed at investigating SMC activation, connectivity and plasticity with regard to motor initiation in FOG. Methods: Twelve patients with FOG and eleven without FOG underwent a multimodal electrophysiological evaluation of SMC functioning including the Bereitschaftspotential and movement-related desynchronisation of cortical beta oscillations. SMC plasticity was modulated by intermittent theta burst stimulation (iTBS) and its impact on gait initiation was assessed by a three-dimensional gait analysis. Results: Prior to volitional movements the Bereitschaftspotential was smaller and beta power was less strongly attenuated over the SMC in patients with FOG compared to those without. Pre-motor coherence between the SMC and the primary motor cortex in the beta frequency range was also stronger in patients with FOG. iTBS resulted in a relative deterioration of gait initiation. Conclusions: Reduced activation of the SMC along with increased SMC connectivity in the beta frequency range hinder a flexible shift of the motor set as it is required for gait initiation. Significance: Altered SMC functioning plays an important role for motor initiation failure in PD-related FOG.